Imaging Findings in Giant Cell Arteritis: Don’t Turn a Blind Eye to the Obvious! - Bathla, Girish; Agarwal, Amit K.; Messina, Steven A.; Black, David F.; Soni, Neetu; Diehn, Felix E.; Campeau, Norbert G.; Lehman, Vance T.; Warrington, Kenneth J.; Rhee, Rennie L.; Bley, Thorsten A. (American Journal of Neuroradiology, 2025)
Giant cell arteritis (GCA) is the most common primary large vessel systemic vasculitis in the Western World. Even though the involvement of scalp and intracranial vessels has received much attention in the neuroradiology literature, GCA, being a systemic vasculitis, can involve multiple other larger vessels including the aorta and its major head and neck branches. Herein, the authors present a pictorial review of the various cranial, extracranial, and orbital manifestations of GCA. An increased awareness of this entity may help with timely and accurate diagnosis, helping expedite therapy and preventing serious complications.ACRAmerican College of RheumatologyAIONanterior ischemic optic neuropathyESRerythrocyte sedimentation rateEULAREuropean League Against RheumatismGCAgiant cell arteritisLV-GCAlarge vessel GCAPMRpolymyalgia rheumaticaTABtemporal artery biopsyVWIvessel wall imagingSTAsuperficial temporal artery